Cognitive, collaborative, conceptual and creative — Four characteristics of the next generation of knowledge-based CAD systems: A study in biologically inspired design - Goel, Ashok K.; Vattam, Swaroop; Wiltgen, Bryan; Helms, Michael (Computer aided design, 2012)
We envision that the next generation of knowledge-based CAD systems will be characterized by four features: they will be based on cognitive accounts of design, and they will support collaborative design, conceptual design, and creative design. In this paper, we first analyze these four dimensions of CAD. We then report on a study in the design, development and deployment of a knowledge-based CAD system for supporting biologically inspired design that illustrates these four characteristics. This system, called DANE for Design by Analogy to Nature Engine, provides access to functional models of biological systems. Initial results from in situ deployment of DANE in a senior-level interdisciplinary class on biologically inspired design indicates its usefulness in helping designers conceptualize design of complex systems, thus promising enough to motivate continued work on knowledge-based CAD for biologically inspired design. More importantly from our perspective, DANE illustrates how cognitive studies of design can inform the development of CAD systems for collaborative, conceptual, and creative design, help assess their use in practice, and provide new insights into human interaction with knowledge-based CAD systems. ► Biologically inspired design uses analogies to biological systems. ► In SBF models, functions act as indices to knowledge of structure and behaviors. ► We deployed DANE in a course on biologically inspired design. ► DANE’s SBF models could be useful for conceptualizing biological systems. ► The value of SBF models may lie in enabling designers to organize their knowledge.